45.7k views
2 votes
If f(x) = 3x + 7 and g(x) = 5x – 2 then (f+g)(x) = 8x + 5. True False

User KuKu
by
5.7k points

2 Answers

7 votes
You are adding together functions f(x) and g(x) as follows:

f(x) + g(x) = 3x + 7 + 5x - 2. Combining like terms, 3x+5x=8x, and -2+5=3.

Thus, (f+g)(x) = 8x + 5. What is your conclusion?
User Dzumret
by
6.2k points
2 votes

Answer: The given statement is TRUE.

Step-by-step explanation: We are given the following two functions :


f(x)=3x+7,~~~\textup{and}~~~g(x)=5x-2.

We are to check whether the following statement is true or false :


(f+g)(x)=8x+5.

We know that for any two functions p(x) and q(x), we have


(p+q)(x)=p(x)+q(x).

Therefore, we get


(f+g)(x)\\\\=f(x)+g(x)\\\\=(3x+7)+(5x-2)\\\\=3x+7+5x-2\\\\=8x+5.

Thus,
(f+g)(x)=8x+5.

The given statement is TRUE.

User Ajay Singh Mehra
by
4.9k points